Improving membrane bioreactor performance through the synergistic effect of silver-decorated graphene oxide in composite membranes. (April 2020) - Mahmoudi, Ebrahim; Ng, Law Yong; Ang, Wei Lun; Teow, Yeit Haan; Mohammad, Abdul Wahab
Highlights: Graphene oxide decorated with silver could act as nanofiller in PES membranes. Modified membranes showed significant improvement in anti-biofouling. Modified membranes have higher zeta potential and more hydrophilic. Modified membranes have great potential in developing high-performance MBR. Abstract: Membrane bioreactors (MBRs) have emerged as more sustainable alternatives to conventional water treatment methods due to their lower footprint and higher capacity. However, biofouling of the membranes results in reduced membrane lifespan, thus leading to higher operating costs. In this work, the synergistic effect of silver decoration on graphene oxide (GO) in polyether sulfone (PES) membranes was demonstrated to significantly reduce biofouling and enhance other membrane properties. The PES membranes containing different amounts (0.00–2.5 wt %) of silver-decorated GO (Ag-GO) were fabricated by a wet-phase inversion fabrication method. The membrane contact angle was reduced from 67 ± 3.59˚ for pure PES to 39 ± 2.9˚ for a Ag-GO PES membrane, which is an indication of a significant increase in hydrophilicity. The Ag-GO PES membranes became more negatively charged with increasing Ag-GO content, reaching –34.3 mV at a concentration of 2.5 wt % Ag-GO. Water flux and rejection were enhanced for the Ag-GO-embedded membranes. After 20 h of MBR operation, permeation of the pure PES membrane stopped completely, while the modified Ag-GO PES membranes showed longer resistance against fouling. The modified membranes showed great potential to contribute towards higher performance and more sustainable MBR operation.